MENGENAL RAGAM GERAK DAN JALINAN ESTETIKA TARI BALI (LPPM IKIP PGRI Bali, 2018)
Motion is the main element as an expression medium in dance, so the motionvariety is very important to be known in understanding theBalinese dance. Balinese dance as a performance art is an aesthetic variety of various motions in its performance. Therefore, this paper aims to reveal the variety of Balinese dance motions and aesthetic braidingcontained in it. The problems in this study are we must know the various motions of Balinese dance and the forms of aesthetic braiding in it.   To explain the objectives and problems in this paper, library methods that are based on qualitative research will be used on the basis of symbolic interaction theory analysis. The analysis result of this paper is the motion varieties of Balinese dance is a form of stylization of natural motions in their environment which are esthetically interwoven in the performance of artwork as a unity in balance of the stage design.